Analysis of The Qur’an Tutorial Planning Management and Fiqh of Worship At The Sultan Agung Islamic University - Imam, Atfalul; Joko Raharjo, Tri; Yulianto, Arief (Educational Management, 2021)
This study aims to analyze the planning management of the al-Qur’an tutorial program and fiqh of worship at Sultan Agung Islamic University Semarang. This study uses a qualitative case study approach. The research subjects consisted of the Head of the al-Qur’an Tutorial Division, tutor coordinator, tutor/mentor and tutorial participants. The data collection technique used the interview method, observation, and document analysis. The research instrument was the researcher and the interview guide, observation and document analysis. The validity of the data was done by triangulating the source and triangulating the findings. Data analysis used interactive Miles-Huberman analysis consisting of data reduction, data presentation, and conclusion drawing. The results showed that the management planning of the tutorial program al-Qur'an and fiqh of worship at the Islamic University of Sultan Agung Semarang was guided by: (1) Analysis of student needs/problems (2) Analysis of the conditions and situation of the university, (3) Determination of objectives, (4) ) Determining the type, technique and strategy of activities, (5) Determining the time and place of activities, (6) Determining facilities and budgeting costs.